Feline Otitis Externa Caused by Methicillin-Resistant Staphylococcus aureus with Mixed Hemolytic Phenotype and Overview of Possible Genetic Backgrounds - Jana Avberšek; Bojan Papić; Darja Kušar; Vladimira Erjavec; Katja Seme; Majda Golob; Irena Zdovc (MDPI AG, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) is an important cause of nosocomial infections in humans, but its importance in small animal practice is increasing. Here, we present a case of feline otitis externa (OE) caused by MRSA; both hemolytic and nonhemolytic variants with a stable phenotype were recovered from the external auditory canal after infection was detected by routine otoscopy. One isolate per variant underwent antimicrobial susceptibility testing (AST) by broth microdilution method, conventional spa typing and whole-genome sequencing (WGS). The results showed that both variants were genetically related and were of sequence type (ST) 1327, SCCmec type IV and spa type t005. AST and WGS showed that both isolates were resistant to β-lactams and sensitive to all tested non-β-lactam antibiotics. Both isolates were pvl-negative, but encoded several other virulence genes (aur, hlgABC, sak, scn, seg, sei, sem, sen, seo and seu). Genetic background of the mixed hemolytic phenotype was not identified; no differences in the agr locus or other regulatory regions were detected. Three single-nucleotide polymorphisms were identified but could not be associated with hemolysis. This well-documented case of MRSA infection in companion animals adds to the reports of MRSA infections with a mixed hemolytic phenotype.